Ethics, "Vulnerability, " and Feminist Participatory Action Research With a Disability Community. (July 2014) - Gustafson, Diana L.; Brunger, Fern
We consider the work of research ethics boards and funding models for research that at times are incompatible with the relationship building required for feminist participatory action research with a disability community. We explore the barriers that emerged for university- and community-based partners as they asserted individual and collective identities, and negotiated boundaries, access, and power relations in the process of designing and conducting research. This critical reflection contributes to our understanding of the structures of academic research funding, ethics approval, and how problematic conceptualizations of vulnerability embedded in the Tri-Council Policy Statement and research ethics board practices impact on relationship building and the research process. Recommendations for change will be helpful to researchers studying disability, those using participatory action research, and individuals serving on ethics review boards.